Lack of evidence for an increased microchimerism in the circulation of patients with Sjögren's syndrome. Issue 3 (1st March 2001) - Toda, I; Kuwana, M; Tsubota, K; Kawakami, Y
Abstract : OBJECTIVE: To examine the hypothesis that fetal microchimerism plays a part in the pathogenic process of Sjögren's syndrome (SS). METHODS: Genomic DNA samples were extracted from peripheral blood whole nucleated cells and the CD34+ cell enriched fraction of patients with SS and healthy women who had male offspring as well as nulliparous women. A Y chromosome-specific sequence was detected as a marker for fetal cells by a nested polymerase chain reaction (PCR) and by DNA hybridisation combined with PCR using specific primers and probes. All procedures were performed with great care to avoid the contamination of male DNA. RESULTS: A nested PCR and DNA hybridisation combined with PCR was established that can detect a single male cell out of 1.67×10 5 female cells. It was not possible to increase the sensitivity further because the amount of template DNA held in the PCR was limited. When these methods were used, no fetal cells were detected in any samples from patients with SS, though they were detected in whole nucleated cells from two healthy women who had delivered sons previously. CONCLUSIONS: The findings indicate that circulating fetal cells in patients with SS are uncommon ( < 1 in 1.67×10 5 ), if they exist. With the conventional PCR based methods that were used, it is difficult to evaluate the quantitative difference in circulating fetal cells between patients with SS and healthy women.